Managing Conflicts with Wildlife: Living with Coyotes - Lauren Watine; William M. Giuliano; Holly K. Ober; Raoul Boughton; Alexander Gulde; Angeline Scotten (EDIS)
The omnivorous coyote is a relative newcomer to Florida that plays an important role in ecosystems and food webs. Of particular importance and possible benefit may be their potential ability to control populations of pest species such as some rodents. Although rare, there are situations where coyotes can become dangerous or damaging. In this 4-page fact sheet, we present some facts about coyotes, describe dangers and problems they may cause, and provide suggestions on how to cope with these issues. Written by Lauren Watine, William M. Giuliano, Holly K. Ober, Raoul Boughton, Alexander Gulde, Angeline Scotten, and published by the UF Department of Wildlife Ecology and Conservation, December 2014. (Photo: W. M. Giuliano, UF/IFAS)